2003
DOI: 10.1136/jme.29.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Non-heart beating organ donation: old procurement strategy—new ethical problems

Abstract: The imbalance between supply of organs for transplantation and demand for them is widening. Although the current international drive to re-establish procurement via non-heart beating organ donation/donor (NHBOD) is founded therefore on necessity, the process may constitute a desirable outcome for patient and family when progression to brain stem death (BSD) does not occur and conventional organ retrieval from the beating heart donor is thereby prevented. The literature accounts of this practice, however, raise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 64 publications
0
28
0
1
Order By: Relevance
“…This can depress the patient's respiratory drive. 2 Anticoagulants (e.g., heparin) might be administered to prevent thrombotic obstruction of blood vessels that can occur after the arrest of circulation. This treatment might aggravate bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…This can depress the patient's respiratory drive. 2 Anticoagulants (e.g., heparin) might be administered to prevent thrombotic obstruction of blood vessels that can occur after the arrest of circulation. This treatment might aggravate bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…First, it appears to violate the principle of nonmaleficence by causing harm to the patient, or at least exposing the patient to potential harm, with no corresponding benefit. 21,24,25 Second, it appears to violate our obligation to act only in our patients' interests and not those of another (in this case, a potential recipient). 22 Because of these issues, some have suggested that any antemortem intervention not for the benefit of the patient is forbidden.…”
Section: Ethical Concerns Regarding Controlled Dcdmentioning
confidence: 99%
“…21,22 Finally, argue supporters of DCD, such protocols allow the health care team to honor the wishes not only of patients, but also of family members who would like to donate the organs of their loved ones. 22,23 Because relatives of the deceased may derive comfort from knowing that their relatives became organ donors, there is ethical value in facilitating this process.…”
Section: Ethical Benefits Of Dcdmentioning
confidence: 99%
See 1 more Smart Citation
“…The problematical aspects of NHBOD referred to above have been described previously [3] and widely debated within the intensive care community [4]. Nevertheless, in its published guidelines, the Intensive Care Society in the UK has given its unequivocal endorsement to NHBOD [5].…”
mentioning
confidence: 98%